2010
DOI: 10.2478/s11532-009-0122-z
|View full text |Cite
|
Sign up to set email alerts
|

Carbon ceramic electrode incorporated with zeolite ZSM-5 for determination of Piroxicam

Abstract: Abstract:A new chemically modified electrode is constructed based on carbon ceramic electrode incorporated with zeolite ZSM-5. Voltammetric behavior of piroxicam at the carbon ceramic zeolite modified electrode (CCZME) was investigated. The modified electrode exhibited catalytic activity toward the electrooxidation of piroxicam. Experimental parameters such as solution pH, scan rate, concentration of piroxicam and zeolite amount were studied. It has been shown that using the CCZME, piroxicam can be determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Piroxicam molecule contains functional groups which are more interesting in view of electrochemical study and the electro-oxidation of piroxicam has been investigated by various studies. [11][12][13][39][40][41][42][43][44][45] The electrochemical oxidation of piroxicam shows an anodic peak at the positive moving step without any cathodic peak on the reverse scan, which indicated that the oxidation reaction is irreversible. Hence, the anodic peak current was used for determination of piroxicam.…”
Section: Resultsmentioning
confidence: 99%
“…Piroxicam molecule contains functional groups which are more interesting in view of electrochemical study and the electro-oxidation of piroxicam has been investigated by various studies. [11][12][13][39][40][41][42][43][44][45] The electrochemical oxidation of piroxicam shows an anodic peak at the positive moving step without any cathodic peak on the reverse scan, which indicated that the oxidation reaction is irreversible. Hence, the anodic peak current was used for determination of piroxicam.…”
Section: Resultsmentioning
confidence: 99%
“…19 K. Asadpour-Zeynali and co-workers proposed also carbon ceramic electrode modified using zeolite-ZSM-5. 20 In all cases the positive influence of zeolite on z E-mail: justynarobak@poczta.fm electrode sensitivity was confirmed. Nevertheless, so far ferrieritemodified carbon ceramic electrodes have not been investigated.…”
mentioning
confidence: 78%